The use of a static measure to predict foot posture at midstance during walking. (August 2016) - McPoil, Thomas G.; Ford, Jessica; Fundaun, Joel; Gallegos, Chelsea; Kinney, Andrew; McMillan, Peter; Murphy, Jessica; Sky, Elliot; Torba, Derrick; Bade, Michael
Graphical abstract: Highlights: It is unknown if the LAA can predict dynamic foot posture during activity for different foot types. The clinical method used to assess the LAA has high levels of reliability with more than one rater. The LAA measured in relaxed standing is highly predictive of foot posture at midstance while walking for different foot types. Abstract: Previous studies have successfully used the longitudinal arch angle (LAA) to assess foot posture, but the measurement consistency and ability of the LAA to predict dynamic foot posture during activity in a variety of foot types have not been evaluated. The purpose of this study was to determine the reliability of the LAA as well as if the clinical method of assessing the LAA could be used to predict the LAA at midstance during walking for supinated, normal, and pronated foot types. The Arch Height Ratio was used to select 35 participants with 12 supinated, 46 normal, and 12 pronated feet. A standard goniometer was used to measure the LAA (CLINIC_LAA) on both feet while standing. Both feet were then filmed using a high speed camera while walking on a treadmill. The LAA was determined by the angle formed by two lines drawn between the markers placed on the first metatatarsal and medial malleolus with the apex the navicular tuberosity. The LAA in midstance (WALK_LAA) was determined using the mean of five walking trials. The reliability of the CLINIC_LAA assessed on both feet by two raters over two days were excellent. There was no difference between the left and right foot for the CLINIC_LAA. The Pearson correlation between CLINIC_LAA and WALK_LAA for all 70 feet was r = 0.96 (r 2 = 0.92). The results indicate the LAA is highly predictive of foot posture at midstance in walking explaining over 90% of the variance for a wide range of foot types.